School psychology, aesthetics of sensitivity and the decolonial perspective - Silva, Antonio Carlos Barbosa da [UNESP]; Silva, Marina Coimbra Casadei Barbosa da (Editora Univ Leopoldlanum, 2023)
This text proposes to reflect on colonizing education, the aesthetics of sensitivity and the possibility of a decolonial school psychology. Western education serves colonizing purposes that impose conservative, liberal and indoctrinating thinking. The aesthetics of sensitivity was an edu- cational foundation incorporated into the school curriculum in the last two decades and had the function of fostering new processes of subjectivation in students, preparing them to deal with the technological society that grows exponentially and adapting subjects to new skills in the market. work in the globalized world. Along with this strategy of subjective modeling, we also have school psychology, which has always been in tune with the strategies of capitalist society. School psycho- logy, historically, has developed actions to equalize learning differences through standardization, classification and exclusion, sometimes causing the failure of students with fewer financial resources and, consequently, with fewer institutional support networks. The relevance of this debate is justified by the stance of school psychology that still operates in maintaining a colonizing educational system and adapting students' subjectivities to the current capitalist model, which sometimes works in a prescriptive tone associated with the practice of clinical psychology, classificatory, often pathologi- zing, transferring the responsibility for their inadequacy to the new technological society to students. We seek to think that education can be transformed if we combine the aesthetics of sensitivity and critical school psychology as adjuvants for psychosocial practices.
Keywords: School psychology; Aesthetics of sensitivity; Decoloniality